2021
DOI: 10.3389/fpubh.2021.628700
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Incidence, Burden and Cost of Care: A Filipino Community-Based Study

Abstract: Background: In the midst of competing priorities and limited resources in low-middle-income countries (LMIC), convincing epidemiological evidence is critical for urging governments to develop national dementia plans. The majority of primary epidemiological studies on dementia are from high income countries (HIC). Implications for developing countries are typically extrapolated from these outcomes through modeling, meta-analyses, and systematic reviews. In this study, we directly assessed the incidence of demen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Further searches were conducted within these results using the additional search terms "caregiver," "caregiver burden," "stress," "behavioral and psychological symptoms of dementia," "BPSD," "economic," "financial," "autonomy," "dignity," "identity," "personhood" and "ethics." By this method, a total of 103 citations were retained (Pereira, 2011;Schuurmans et al, 2021;Kemmelmeier et al, 2002;Bradley, 2009;Baeke et al, 2011;Chakraborty et al, 2017;Madadin et al, 2020;Nichols, 2013;Emanuel et al, 2000;Krag, 2014;Trachtenberg and Manns, 2017;Bilchik, 1996;Lazar and Davenport, 2018;Karrer et al, 2020;Stakišaitis et al, 2019;Finucane et al, 2007;Finucane, 1999;Sachs et al, 2004;Dominguez et al, 2021;Meier, 1997;Liu et al, 2020;Gao et al, 2019;Gilhooly et al, 2016;Watson et al, 2019;Cheng, 2017;Biggs et al, 2019;Fam et al, 2019;Dening et al, 2013;Owen et al, 2001;Cohen-Mansfield and Brill, 2020;Anderson et al, 2019;O'Dwyer et al, 2016;Bravo et al, 2018;Wicher and Meeker, 2012;Stolz et al, 2015;Seike et al, 2021;Kashimura et al, 2021;Zwingmann et al, 2018;…”
Section: Pitfalls Inherent In the Practice Of Pas In The Specific Case Of Dementiamentioning
confidence: 99%
See 2 more Smart Citations
“…Further searches were conducted within these results using the additional search terms "caregiver," "caregiver burden," "stress," "behavioral and psychological symptoms of dementia," "BPSD," "economic," "financial," "autonomy," "dignity," "identity," "personhood" and "ethics." By this method, a total of 103 citations were retained (Pereira, 2011;Schuurmans et al, 2021;Kemmelmeier et al, 2002;Bradley, 2009;Baeke et al, 2011;Chakraborty et al, 2017;Madadin et al, 2020;Nichols, 2013;Emanuel et al, 2000;Krag, 2014;Trachtenberg and Manns, 2017;Bilchik, 1996;Lazar and Davenport, 2018;Karrer et al, 2020;Stakišaitis et al, 2019;Finucane et al, 2007;Finucane, 1999;Sachs et al, 2004;Dominguez et al, 2021;Meier, 1997;Liu et al, 2020;Gao et al, 2019;Gilhooly et al, 2016;Watson et al, 2019;Cheng, 2017;Biggs et al, 2019;Fam et al, 2019;Dening et al, 2013;Owen et al, 2001;Cohen-Mansfield and Brill, 2020;Anderson et al, 2019;O'Dwyer et al, 2016;Bravo et al, 2018;Wicher and Meeker, 2012;Stolz et al, 2015;Seike et al, 2021;Kashimura et al, 2021;Zwingmann et al, 2018;…”
Section: Pitfalls Inherent In the Practice Of Pas In The Specific Case Of Dementiamentioning
confidence: 99%
“…For the purpose of the review and analysis presented below, the PubMed, ProQuest and Scopus literature databases were searched using the broad search terms “dementia” AND either “euthanasia,” “assisted suicide,” “physician-assisted suicide” or “medical assistance in dying.” After removal of duplicates, a total of 642 citations were retrieved via this initial search. Further searches were conducted within these results using the additional search terms “caregiver,” “caregiver burden,” “stress,” “behavioral and psychological symptoms of dementia,” “BPSD,” “economic,” “financial,” “autonomy,” “dignity,” “identity,” “personhood” and “ethics.” By this method, a total of 103 citations were retained ( Pereira, 2011 ; Schuurmans et al, 2021 ; Kemmelmeier et al, 2002 ; Bradley, 2009 ; Baeke et al, 2011 ; Chakraborty et al, 2017 ; Madadin et al, 2020 ; Nichols, 2013 ; Emanuel et al, 2000 ; Krag, 2014 ; Trachtenberg and Manns, 2017 ; Bilchik, 1996 ; Lazar and Davenport, 2018 ; Karrer et al, 2020 ; Stakišaitis et al, 2019 ; Finucane et al, 2007 ; Finucane, 1999 ; Sachs et al, 2004 ; Dominguez et al, 2021 ; Meier, 1997 ; Liu et al, 2020 ; Gao et al, 2019 ; Gilhooly et al, 2016 ; Watson et al, 2019 ; Cheng, 2017 ; Biggs et al, 2019 ; Fam et al, 2019 ; Dening et al, 2013 ; Owen et al, 2001 ; Cohen-Mansfield and Brill, 2020 ; Anderson et al, 2019 ; O'Dwyer et al, 2016 ; Bravo et al, 2018 ; Wicher and Meeker, 2012 ; Stolz et al, 2015 ; Seike et al, 2021 ; Kashimura et al, 2021 ; Zwingmann et al, 2018 ; Gitlin et al, 2019 ; von Känel et al, 2019 ; Zwingmann et al, 2019 ; Gerk, 2017 ; Kipke, 2015 ; Deardorff and Grossberg, 2019 ; Tiel et al, 2015 ; Borroni et al, 2008 ; Kim et al, 2021 ; Yunusa et al, 2019 ; Seibert et al, 2021 ...…”
Section: Pitfalls Inherent In the Practice Of Pas In The Specific Case Of Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…In a population-based cohort study of Filipino older adults, aged ≥ 60 years, we found a dementia prevalence of 10.6% ( 5 ), much higher than the 7% estimate for Southeast Asia ( 2 ), and 23.2% had mild cognitive impairment (MCI). Almost half (48.1%) of those with baseline MCI status, from the same cohort, developed incident dementia after 3–4 years of follow-up ( 6 ) indicating MCI as a potentially progressive condition that makes older individuals at high risk for developing dementia ( 7 ). Progression from MCI to dementia occurs at a higher rate with an estimated conversion rate of 10–15% per year ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Progression from MCI to dementia occurs at a higher rate with an estimated conversion rate of 10–15% per year ( 7 , 8 ). The odds of progressing to dementia is increased by 3.07 times among those with MCI ( 6 ) and further increased by 1.53–2.95 times higher if identified with comorbid conditions such as cardiovascular risks and metabolic syndrome ( 9 ). This condition is prevalent in Filipino older adults, with around 82.0% of men and 70.4% of women having at least one cardiovascular risk factor (hypertension, diabetes, dyslipidemia, and smoking) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%